PERSEPSI STAKEHOLDER PADA PENGEMBANGAN PUSAT KONSERVASI GAJAH DI KHDTK AEK NAULI - Rospita Odorlina Situmorang; Johansen Silalahi; Wanda Kuswanda (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Aek Nauli Special Purpose Forest (KHDTK) that is located around Lake Toba is currently being developed to conserve Sumatran elephants through ecotourism. This study aimed to examine stakeholders’ perception on the development of elephant ecotourism, analyze the correlation of respondents’ socio-economic characteristic toward perception, and recommend the development of Elephant Conservation Center at KHDTK Aek Nauli. The study was conducted by using quantitative deductive approach through survey data collection method.  Data were analyzed using frequency analysis and Spearman’s rank correlation. Overall, the results showed that stakeholders gave a high perception on the development of the Elephant Centre (2.44 out of a maximum score of 3.00) with the highest perception as follows: tourism, education, economics, and conservation aspects respectively. The entrepreneurs group gave the highest perception since the elephant conservation center potentially to attract tourist to visit Lake Toba, on the other hand, communities and visitors gave the lower perceptions because the area is still new and community involvement is still limited. Spearman rank analysis between respondents’ socioeconomic characteristic and level of perception showed that education and income levels influenced the perception with a moderate coefficient. However, for the level of age, the coefficient was very low. This research is important to increase the synergy and participation of  stakeholders to the project.